2023
DOI: 10.1039/d2qo01977a
|View full text |Cite
|
Sign up to set email alerts
|

Binaphthyl-derived armchair-type molecular carbon rings with chirality: synthesis and optical properties

Abstract: Herein, we report the synthesis of binaphthyl-derived hoop-shaped aromatic hydrocarbon enantiomers (RCR, SCR) as segments of (9,9) armchair CNTs. After the structures were identified by HR-MS and NMR, further circular...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Unlike the previously reported chiral carbon nanotubes (CNTs), which derive their chirality from the lack of a plane of symmetry or a molecular inversion center, Du and Xu [ 25 ] have recently synthesized two armchair carbon ring CNTs ( R ‐ 39 and S ‐ 39 ) ( Figure ). Geometry optimization and NMR spectrums revealed that the two OEt groups were located in the inner and outer sides of nanorings.…”
Section: π‐Conjugated Chiral Macrocycles In Circularly Polarized Lumi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the previously reported chiral carbon nanotubes (CNTs), which derive their chirality from the lack of a plane of symmetry or a molecular inversion center, Du and Xu [ 25 ] have recently synthesized two armchair carbon ring CNTs ( R ‐ 39 and S ‐ 39 ) ( Figure ). Geometry optimization and NMR spectrums revealed that the two OEt groups were located in the inner and outer sides of nanorings.…”
Section: π‐Conjugated Chiral Macrocycles In Circularly Polarized Lumi...mentioning
confidence: 99%
“…CD spectra and the structures of enantiomers of R ‐ 39 and S ‐ 39 . [ 25 ] Reproduced with permission. [ 25 ] Copyright 2023, the Royal Society of Chemistry.…”
Section: π‐Conjugated Chiral Macrocycles In Circularly Polarized Lumi...mentioning
confidence: 99%
“…Nanorings 6 n displays size‐dependent photophysical properties and is synthesized directly through platinum‐mediated assembly of BINOL derivative 5 units. Our ongoing efforts aim to introduce chirality into armchair‐type CNT segments by incorporating BINOL chiral units, thereby broadening the scope of CNT segments with chiral attributes [31] . The enantiomers ( R )/( S )‐ 7 were successfully synthesized and characterized through circular dichroism (CD) spectral analysis.…”
Section: Binol‐based Chiral Macrocyclesmentioning
confidence: 99%
“…Our ongoing efforts aim to introduce chirality into armchair-type CNT segments by incorporating BINOL chiral units, thereby broadening the scope of CNT segments with chiral attributes. [31] The enantiomers (R)/(S)-7 were successfully synthesized and characterized through circular dichroism (CD) spectral analysis. Additionally, the Φ PL of compound 7 was determined to be 54 % (Figure 3b).…”
Section: Binol-based Chiral Macrocyclesmentioning
confidence: 99%